2016
DOI: 10.1186/s40246-016-0080-4
|View full text |Cite
|
Sign up to set email alerts
|

Experience of a multidisciplinary task force with exome sequencing for Mendelian disorders

Abstract: Background: In order to optimally integrate the use of high-throughput sequencing (HTS) as a tool in clinical diagnostics of likely monogenic disorders, we have created a multidisciplinary "Genome Clinic Task Force" at the University Hospitals of Geneva, which is composed of clinical and molecular geneticists, bioinformaticians, technicians, bioethicists, and a coordinator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 20 publications
1
31
0
2
Order By: Relevance
“…However, if the panel was more costly than clinical GWS, the patient was classified as appropriate for clinical GWS. This is similar to the triage strategy adopted at University Hospitals of Geneva, where costing is a component of the consideration (Fokstuen et al., ). Patients eligible for high‐throughput sequencing included those with a likely heterogeneous Mendelian disorder with at least one known clearly pathogenic gene and patients with developmental delay of unknown origin, but the cost of performing high‐throughput sequencing needed to be less than the Sanger sequencing of the corresponding genes (Fokstuen et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, if the panel was more costly than clinical GWS, the patient was classified as appropriate for clinical GWS. This is similar to the triage strategy adopted at University Hospitals of Geneva, where costing is a component of the consideration (Fokstuen et al., ). Patients eligible for high‐throughput sequencing included those with a likely heterogeneous Mendelian disorder with at least one known clearly pathogenic gene and patients with developmental delay of unknown origin, but the cost of performing high‐throughput sequencing needed to be less than the Sanger sequencing of the corresponding genes (Fokstuen et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, implementation of a combined complex test review and genetic consultation service (with a genetic counselor performing the initial review) within a clinical center has been shown to reduce the number of inappropriate tests, shorten time to diagnosis, and exert a positive influence on health care provider's behaviors (Suarez, Yu, Downs, Costa, & Stevenson, ). A multidisciplinary approach to triage patients for GWS similar to the Genomic Consultation Service has also been used elsewhere, although the impact of triage on the cost efficiency of GWS was not evaluated in those cases (Bowdin et al., ; Fokstuen et al., ; Lazaridis et al., ; Ormondroyd et al., ). The average presentation time per patient was 7 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now there have been at least 15 reported genetic variants of PIGA in clinical PIGA deficiency cases with most of which having been experimentally proven as pathogenic variants (Figure c). All these reported disease‐associated variants are located in the coding exons, including 10 missense variants at conserved positions of PIGA protein (NP_002632.1: p.Arg77Leu, p.Pro93Leu, p.Arg119Trp, p.(Ala142Thr), p.(Lys143Glu), p.Asn179Tyr, p.Ile206Phe, p.(Ser330Asn), p.(Glu395Lys), p.(Ile451Thr)), one in‐frame deletion (p.(Leu344del)), two duplications causing frame‐shifts (p.(Ser24Lysfs*3), p.Tyr26Leufs*3), and one non‐sense variant (p.Arg412*) (Figure b) (Fokstuen et al., ; Joshi et al., ; Kim et al., ; Olson et al., ; Soden et al., ; Zhu et al., ). In addition, there has also been one de novo missense variant (p.(Leu355Ser)) which has PIGA deficiency phenotype (Trump et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Up to now there have been at least 15 reported genetic variants of PIGA in clinical PIGA deficiency cases with most of which having been experimentally proven as pathogenic variants (Figure 2c). All these reported diseaseassociated variants are located in the coding exons, including 10 missense variants at conserved positions of PIGA protein (NP_002632.1: p.Arg77Leu, p.Pro93Leu, p. (Figure 2b) (Fokstuen et al, 2016;Joshi et al, 2016;Kim et al, 2016;Olson et al, 2017;Soden et al, 2014;Zhu et al, 2015). In addition, there has also been one de novo missense variant (p.(Leu355Ser)) which has PIGA deficiency phenotype (Trump et al, 2016).…”
Section: Discussionmentioning
confidence: 99%